DIGITAL INCLUSION IN STUDENTS WITH SPECIAL NEEDS IN BRAZILIAN PUBLIC SCHOOLS - do Nascimento Prado, Roselândia; Pinho Neto, Gisélia; Farias Santos da Silva, Adriana; Maria Monteiro da Silva, Gilvana; José Melo dos Santos, Mozart; Carlos Vanderlei da Silva, José; da Silva Lima, Almir; da Silva Costa, Joselma; Afonso Alves Geronimo, Manuel; Januária da Silva Araujo, Silvia (Revista Gênero e Interdisciplinaridade, 2024)
This article addresses the concepts of the use of educational information technology in Brazil and its relationship with the socialization of students with special needs. It begins with a report on the historical context of digital inclusion in Brazilian education, highlighting the main policies and programs implemented over the last few decades to integrate technology into the school environment. The research focuses on specific initiatives for the use of IT and related technologies as pedagogical support tools for students with special educational needs, such as Down Syndrome and hyperactivity disorders, in public elementary schools. The methodology used includes a qualitative analysis, with participatory observation in classrooms and semi-structured interviews with teachers, students and the resource room coordinator. The data collected was analyzed to identify the impacts of educational technologies on students’ learning and socialization. In addition, applications and digital tools were mapped that facilitate classes and promote a more inclusive learning environment. The main results indicate that the use of assistive technology has contributed significantly to the cognitive and social development of students, promoting greater interaction and autonomy. Educational applications stand out for their ability to adapt curricular content to individual needs, resulting in more personalized and effective learning. However, the research also identified challenges, such as the need for ongoing training for teachers to effectively use these technologies and the lack of adequate infrastructure in some schools.